2007
DOI: 10.1074/jbc.m610717200
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hemoglobin Allostery in Hypoxia-induced Metabolic Alterations in Erythrocytes

Abstract: When erythrocytes are exposed to hypoxia, hemoglobin (Hb) stabilizes in the T-state by capturing 2,3-bisphosphoglycerate. This process could reduce the intracellular pool of glycolytic substrates, jeopardizing cellular energetics. Recent observations suggest that hypoxia-induced activation of glycolytic enzymes is correlated with their release from Band III (BIII) on the cell membrane. Based on these data, we developed a mathematical model of erythrocyte metabolism and compared hypoxia-induced differences in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 49 publications
5
97
0
1
Order By: Relevance
“…CO has been believed to share varied physiological effects on biological systems with NO. However, through extrapolation of studies in vitro indicating biochemical actions of CO to trigger structural changes in gas-responsive heme proteins (such as sGC, hemoglobin) distinct from those elicited by NO, 7,19,21,22,38 evidence that CO is a unique gaseous regulator distinct from NO has been emerging. In fact, CO itself modestly activates sGC, by which hepatic sinusoids are constitutively dilated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO has been believed to share varied physiological effects on biological systems with NO. However, through extrapolation of studies in vitro indicating biochemical actions of CO to trigger structural changes in gas-responsive heme proteins (such as sGC, hemoglobin) distinct from those elicited by NO, 7,19,21,22,38 evidence that CO is a unique gaseous regulator distinct from NO has been emerging. In fact, CO itself modestly activates sGC, by which hepatic sinusoids are constitutively dilated.…”
Section: Discussionmentioning
confidence: 99%
“…We performed metabolome analyses of tissue lysates collected from snap-frozen livers of mice using contrast-enhanced time of flight/mass spectrometry according to our previous methods. 18,19 Measurements of hepatic H 2 S contents were based on gas chromatography described in our previous method. 14 Biliary flux of bilirubin-IX␣ (BR-IX␣) in bile samples were determined by enzyme-linked immunosorbent assay using the anti-BR-IX␣ monoclonal antibody as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 20,000 g at 4 C for 15 minutes, the supernatants were filtered through 5 kDa cut-off filter (Millipore). Metabolites including those that had at least one 13 C atom in the filtrate were analyzed by using an Agilent CE Capillary Electrophoresis System equipped with an Agilent 1100 series MSD mass spectrometer, as described previously (24). Labeled metabolites containing at least one 13 C atom in a molecule were collectively indicated as 13 …”
Section: Cell Synchronization and Ce/esi/ms Analysismentioning
confidence: 99%
“…Application of metabolomic analyses using capillary electrophoresis/electrospray ionization/mass spectrometry (CE/ESI/MS; refs. 21,22) allows us to determine fluxes of multiple metabolic pathways during cell-cycle progression in vitro (20,23,24). MALDI-IMS analyses of metastatic tumors have shown that the cancer cells in G 1 phase were more active in glycolysis than those in the other phases.…”
Section: Introductionmentioning
confidence: 99%
“…Kinoshita et al (2007) showed the hypoxia-induced consumption of upstream glycolytic substrates, such as glucose 6-phosphate, and increased downstream products, such as phosphoenolpyruvate, in human erythrocytes. Ishii et al (2007) reported on the response of Escherichia coli cells to genetic and environmental perturbations.…”
Section: Anionic Metabolite Analysismentioning
confidence: 99%